HUBUNGAN PERAN BIDAN DAN DUKUNGAN SUAMI TERHADAP PENGGUNAAN IUD DI WILAYAH KERJA PUSKESMAS SRANDAKAN - Nuryanti, Devi; Destia Trisetyaningsih, Anugerah; Vici Virahaju, Mahindria; Nurwiandani, Widy (Yayasan Nuraini Ibrahim Mandiri, 2024)
Indonesia prioritizes the Family Planning (KB) program, especially Long Term Contraceptive Methods (MKJP) such as the Intrauterine Device (IUD). The use of IUDs in DI Yogyakarta is more popular even though injectable hormonal contraceptives are still dominant in Indonesia, the Srandakan Community Health Center in Bantul recorded the highest use of IUDs (44.5%). National development targets in the strategic plan and target setting for the 2020-2024 BKKBN program, as well as international agreements in the SDGs development goals to increase participation rates in the use of MKJP, this makes it an important issue for participation in the use of MKJP, especially the IUD, which is a contraceptive device that is considered effective. The availability of information and social support from midwives and husbands is key in increasing the acceptance and continued use of IUD contraception by WUS. This study aims to determine the relationship between the role of midwives and husband's support on the use of IUDs by WUS in the Srandakan Community Health Center Work Area, Bantul Yogyakarta. This research is a quantitative study with a correlational analytical design and a cross-sectional approach. The sampling technique used accidental sampling with a total population of 1,034 WUS and a sample of 92 respondents. The research instrument used a questionnaire. The research results were obtained from the Fisher's Exact Test which showed a significant relationship between the role of the midwife (p=0.019) and husband's support (p= <0.001) on IUD use. Based on these results, it can be concluded that the role of the midwife and the husband's support influence the decision to use IUD contraception.